Modeling of dynamic mass coupled system with Runge-Kutta fourth order (2019)
This paper shows the mathematical modeling process of a mechanical system of masses coupled by two springs and a shock absorber. The process of capture of movement of the mass system coupled with springs was done with software Tracker video analysis and modeling tool. The motion capture of the coupled masses A and B was made with a duration of 20 seconds. A comparison of the results of the movement of the two masses will be established as a first instance, by adjusting trajectories of curves in time using Matlab software and as a second instance a numerical solution of the Mass-Spring model will be established using the Runge Kutta method of 4 order. With this last method, it is expected to achieve a better precision modeling of the initial value problem. Finally, a comparison of the two mathematical models will be made analyzing. © Published under licence by IOP Publishing Ltd.